2012
DOI: 10.1155/2012/232960
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Disorders Associated with Elevated Serum IgG4 Levels Encountered in Clinical Practice

Abstract: IgG4-related disease (IgG4-RD) is a recently described systemic fibroinflammatory disease associated with elevated circulating levels of IgG4 and manifests a wide spectrum of clinical presentations. Although serum IgG4 level has been described to be the most sensitive and specific laboratory test for the diagnosis of IgG4-RD, it is recognized that an elevated serum IgG4 level can be encountered in other diseases. In this study, we sought to identify the frequency of IgG4-RD and other disease associations in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 32 publications
(39 reference statements)
4
66
0
3
Order By: Relevance
“…Raised serum IgG4 levels are considered important in the diagnosis of IgG4-RD, refl ected by their inclusion in the current diagnostic criteria ( 3,(8)(9)(10). However, studies reviewing routine serum IgG4 level requests in France and United States have shown that raised serum IgG4 can be seen in a variety of other conditions (11)(12)(13). Th ere have also been inconsistent reports on the value of serum IgG4 levels in monitoring response to treatment, determining risk of relapse and predicting organ involvement ( 5,13,14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Raised serum IgG4 levels are considered important in the diagnosis of IgG4-RD, refl ected by their inclusion in the current diagnostic criteria ( 3,(8)(9)(10). However, studies reviewing routine serum IgG4 level requests in France and United States have shown that raised serum IgG4 can be seen in a variety of other conditions (11)(12)(13). Th ere have also been inconsistent reports on the value of serum IgG4 levels in monitoring response to treatment, determining risk of relapse and predicting organ involvement ( 5,13,14 ).…”
Section: Introductionmentioning
confidence: 99%
“…19,20 At the same time, IgG4 elevation may also be associated with various unrelated disorders, such as repeated infections, autoimmune disease, allergic conditions, carcinoma, cystic fibrosis with concomitant Pseudomonas aeruginosa, and multicentric Castleman disease. [21][22][23] However, it appears that the serum level of IgG4 is consistently lower in these conditions compared with IgG4-related disease (4135 mg/dL). [21][22][23] The diagnostic criteria for IgG4-related disease are still evolving.…”
mentioning
confidence: 99%
“…[21][22][23] However, it appears that the serum level of IgG4 is consistently lower in these conditions compared with IgG4-related disease (4135 mg/dL). [21][22][23] The diagnostic criteria for IgG4-related disease are still evolving. Two recently proposed classifications are based on elevated levels of serum IgG4 (4135 mg/dl or 41.5 times the normal upper limit); enlargement, mass lesions, or dysfunction in one or more characteristic organs; typical radiographic features; and the histologic presence of a prominent lymphoplasmacytic infiltrate, abundant IgG4-positive plasma cells, storiform swirling fibrosis, and obliterative phlebitis.…”
mentioning
confidence: 99%
“…Etiological associations of mesenteric panniculitis include malignancy, infectious disease, autoimmune disease, vasculitis, cirrhosis, peptic ulcer disease, pancreatitis, abdominal aortic aneurysm, previous abdominal surgery and elevated IgG4 related disease [3] (a fibroinflammatory condition initially associated with autoimmune pancreatitis, but now recognised in a number of conditions including atopic dermatitis, vasculitis, pancreatic cancer, biliary tract disease, and also present in 5% of the normal population) [10].…”
Section: Discussionmentioning
confidence: 99%